Evaluation of the Cost of Comprehensive Outpatient Therapies in Patients with Malignant Brain Tumors. (May 2017) - McCarty, Stacy; Keeshin, Susan; Eickmeyer, Sarah M.; Shahpar, Samman; Semik, Patrick; Wong, Alex W. K.
Abstract : Objective: The aim of this study was to compare the cost of comprehensive outpatient therapy (day rehabilitation) in individuals with malignant brain tumors to those with stroke and traumatic brain injury. Design: This was a prospective, nonrandomized, longitudinal study of 49 consecutive adults with malignant brain tumors enrolled in the 6 day rehabilitation sites of 1 institution over 35 months. The control group was composed of 50 patients with brain injury and 50 patients with stroke, who were also enrolled in the day rehabilitation program during the same period. A comparison was made of the total Medicare cost and the cost per day of day rehabilitation in patients with malignant brain tumors compared with the control group. Results: The patients with malignant brain tumors had lower total cost and cost per day than did the combined traumatic brain injury and stroke group during day rehabilitation (F2, 143 = 3.056 [ P = 0.05] and F2, 142 = 5.046 [ P = 0.008], respectively). Conclusions: The cost of comprehensive outpatient rehabilitation in patients with malignant brain tumors is less expensive than that of patients with traumatic brain injury or stroke, which are neurological diagnoses commonly seen in day rehabilitation. This study shows that cost should not be a barrier to providing outpatient therapies to this patient population.